Lysophosphatidic acid supports the development of vitrified ovarian follicles by decreasing the incidence of cell death: An experimental study - Neda Abedpour; Nassim Ghorbanmehr; Mojdeh Salehnia (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Lysophosphatidic acid (LPA) contributes to follicular activation, oocyte maturation, in vitro fertilization, and embryo implantation. Objective: This study was designed to evaluate the effects of LPA to improve the development of isolated follicles derived from whole mouse cultured vitrified ovaries. Materials and Methods: In this experimental study, first, the 1-wk-old mouse ovaries in the non-vitrified and vitrified groups were cultured in the presence of 20 µM of LPA for 1 wk. Then, their isolated preantral follicles were cultured individually for 12 days in the presence or absence of 40 µM of LPA. The following evaluations were done for the cultured follicles: a viability test using Calcein AM staining, flow cytometry using annexin V/Pi, and analysis of the expression of genes by real-time reverse transcription polymerase chain reaction. The maturation rates of the oocytes were compared among groups and some of the released metaphase II oocytes were subjected to in vitro fertilization. Results: In all LPA treated groups, the rates of survival and follicular development were higher, and the incidence of cell death and expression of pro-apoptotic genes were lower, than in the non-LPA supplemented groups (p = 0.035). There was no significant difference between the vitrified and non-vitrified groups regarding follicular or oocyte development, but the expression of Bad and LPA receptors genes was significantly altered in the vitrified LPA supplemented group in comparison with the non-vitrified LPA supplemented group (p = 0.028). Conclusion: LPA improved the survival and developmental potential of the isolated follicles. Despite some alterations in the expression of apoptosis-related genes in the vitrified ovaries, LPA had positive effects on the survival and development of these follicles.